Assessing the Delayed Gratification, Identity Orientation and Transitional Plans of ESGP-PA Recipients: Implications for Policies and Program Development - ALMA G MARANDA; ODESSA MAY D ESCALONA; ANTONIETTE ZACARINA B SANSONA; JIDDO ANDREI G MARANDA (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2016)
Governments in developing countries adopted the Conditional Cash Transfer (CCT) system to alleviate poverty and reduce the transmission of poverty from one generation to the next. In the Philippines, the ESGP-PA is the government’s version of CCT. The ESGP-PA grant has immense implications to the lives of recipients and it is important to examine the psychological aspects to inform policy making and to assess the effectiveness of the program as perceived by the recipients. This study measured delayed gratification and self-identity orientations using standardized instruments and analyzed using descriptive and inferential statistics. Transitional plans were assessed qualitatively. Results showed that recipients had high levels of delayed gratification for achievement and moderate levels for food, money, physical and social interaction. They had higher personal and relational identity orientations than social and collective identity orientations. Relational identity (r=-.329, p=.000) and collective identity (r=-.363, p=.000) was negatively correlated with delayed gratification while money (F=1.614; p=.004) significantly influenced social identity orientation. They feared they would not reach their dreams, while financial difficulties and economic factors, hindered them from reaching their goals. In conclusion, ESGPPA recipients’ psychological well-being is positively and negatively impacted by the ESGPPA program.